Biodiversity of benthic diatoms and aquatic insects at Mae tuen Stream passing Omkoi District Chiang Mai Province, Thailand - Tatporn Kunpradid (2018)
Copyright © EM International. The biodiversity of benthic diatoms and aquatic insects found at the Mae Tuen Stream as it passes through Omkoi District at Chiang Mai Province in Thailand was investigated on August and November 2013, and March 2014. The samples were collected from 3 locations along the Mae Tuen Stream as it passes through Omkoi District. A total of forty-six species and forty-three families of benthic diatoms and aquatic insects were found respectively. The diversity index of benthic diatoms ranged from 1.53-2.94, while the diversity index of the aquatic insects ranged from 1.14-2.18. At the upstream, the high abundant of both organisms were found indicate the low pollution level and showed high values in terms of the diversity index, while some tolerant organisms were found at the downstream sites. Moreover, the classification of the water quality by using the surface water quality standards of Thailand was in Classl, which indicated the extra clean and without wastewater discharged. This suggests that the water from this water body could be used for the purposes of ecosystem conservation where basic organisms can living naturally.